Rs145204276 and rs4759314 affect the prognosis of prostate cancer by modulating the GAS5/miR-1284/HMGB1 and HOTAIR/miR-22/HMGB1 signalling pathways - Zhi-Hai Deng; Gan-Shen Yu; Bin Pan; Zhen-Hua Feng; Qiang Huang; Jian-Zhong Deng; Bo Chen; Shi-Kun Yang (Artificial Cells, Nanomedicine, and Biotechnology)
Non-coding RNAs play an important role in the pathogenesis of prostate cancer (PC). This study aims to characterize the role of GAS5 rs145204276 and HOTAIR rs4759314 polymorphisms in the pathogenesis of PC. Both INS allele of GAS5 rs145204276 and A allele of HOTAIR rs4759314 were identified to increase the survival of PC patients. And patients carrying DEL/DEL + AG genotypes tend to present higher levels of HMGB1, GAS5, HOTAIR and lower levels of miR-1284 and miR-22. In addition, the transcription activity of GAS5 promoter was increased by the deletion allele of rs145204276 polymorphism, while the G allele of rs4759314 polymorphism increased the transcription activity of HOTAIR promoter. GAS5 and HOTAIR could bind to miR-1284 and miR-22, respectively, while miR-1284 and miR-22 could bind to the 3′UTR of HMGB1. Compared with the control group, the expressions of miR-1284 or miR-22 were decreased with the presence of GAS5 or HOTAIR, and the expression of HMGB1 was the highest in the GAS5 + HOTAIR group. In summary, the findings of this study demonstrated that both GAS5 rs145204276 and HOTAIR rs4759314 polymorphisms could affect the prognosis of PC by modulating the expression of HMGB1 via modulating the GAS5/miR-1284/HMGB1 and HOTAIR/miR-22/HMGB1 signalling pathways.